Sindroma Ovarium Polikistik (PCOS) Pada Remaja Wanita di Indonesia: Tantangan Baru dalam Kesehatan Reproduksi Wanita - Murthi, Aditya Krishna; Wratsangka, Raditya; Sisca, Sisca; Kurniawan, Yani (Fakultas Kedokteran Universitas Trisakti, 2025)
Adolescence is a crucial phase in individual growth and development, especially for young women, who experience significant physical and hormonal changes. These changes impact reproductive health, including the regularity of the menstrual cycle. Menstrual cycle irregularities can be an early manifestation of Polycystic Ovarian Syndrome (PCOS), one of the most common endocrine disorders in women of reproductive age. Hyperandrogenism, ovulatory disorders, and polycystic ovarian morphology characterize PCOS. Its prevalence in adolescents ranges from 6–10% and tends to increase with lifestyle changes such as a high-calorie diet, lack of physical activity, and psychological stress. Pathophysiologically, PCOS involves complex interactions among genetic, epigenetic, and environmental factors that disrupt the balance of hormones LH, FSH, and AMH and cause insulin resistance. This condition triggers hyperandrogenism, inhibits follicular maturation, and leads to chronic anovulation. The diagnosis of PCOS in adolescents requires caution based on the Rotterdam Consensus (2003) and the 2018 International Guidelines, taking into account similarities to the physiological symptoms of puberty. PCOS is strongly linked to obesity, metabolic syndrome, and family history, with insulin resistance playing a significant role in its development. Elevated Anti-Müllerian Hormone (AMH) levels indicate the severity of PCOS and are associated with metabolic disorders. Therefore, a preventive, holistic approach that promotes a healthy lifestyle is essential for adolescents, including education on balanced nutrition, increased physical activity, and stress management. These measures are expected to decrease the occurrence of PCOS and long-term complications such as infertility and metabolic syndrome in young women in Indonesia.